2017
DOI: 10.1159/000481403
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Management of Cardiovascular Disorders

Abstract: Personalized management of cardiovascular disorders (CVD), also referred to as personalized or precision cardiology in accordance with general principles of personalized medicine, is selection of the best treatment for an individual patient. It involves the integration of various “omics” technologies such as genomics and proteomics as well as other new technologies such as nanobiotechnology. Molecular diagnostics and biomarkers are important for linking diagnosis with therapy and monitoring therapy. Because CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Accumulating evidence indicates that alterations in the gene expression linked to atheroma formation are typically driven by dysregulated epigenetic-based mechanisms acting in conjunction with specific transcription factors [47]. Thus, personalized treatment of atherosclerosis based on epigenetic understanding of patient disease has emerged as an important therapeutic strategy in reducing the burden of CVD [48].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that alterations in the gene expression linked to atheroma formation are typically driven by dysregulated epigenetic-based mechanisms acting in conjunction with specific transcription factors [47]. Thus, personalized treatment of atherosclerosis based on epigenetic understanding of patient disease has emerged as an important therapeutic strategy in reducing the burden of CVD [48].…”
Section: Discussionmentioning
confidence: 99%
“…While the standard CHD medications (statins, antiplatelets, ACE inhibitors, beta blockers, etc.) greatly reduce the risk of complications arising from CHD, side-effects can greatly reduce quality of life (33). Evidence has shown that environmental factors, genomes, and epigenetics play crucial roles in it etiology (27).…”
Section: Discussionmentioning
confidence: 99%
“…Values are means ± SEM; n = 5-7/group exists, particularly with respect to sex. Understanding and identifying genes, gene products, and enzymatic activities involved in the differential responses to RAS inhibitors could improve our knowledge of how drugs differentially affect patients exposed to environmental stressors (e.g., airborne infectious agents such as SARS-CoV-2) by sex [129]. Ironically, RAS inhibition that enhances tissue ACE2 may be a means to protect the heart and lung.…”
Section: Ras Blockade and Covid-19 Outcomesmentioning
confidence: 99%
“…While the RAS plays a key role in the development and progression of CVD, substantial variability in individual responses to ACEi and ARBs exists, particularly with respect to sex. Understanding and identifying genes, gene products, and enzymatic activities involved in the differential responses to RAS inhibitors could improve our knowledge of how drugs differentially affect patients exposed to environmental stressors (e.g., airborne infectious agents such as SARS-CoV-2) by sex [ 129 ].…”
Section: Ras Blockade and Covid-19 Outcomesmentioning
confidence: 99%